Exploring the therapeutic mechanisms of heart failure with Chinese herbal medicine: a focus on miRNA-mediated regulation - Wang, Yang; Lai, Junyu; Chen, Zhengtao; Sun, Liqiang; Ma, Yirong; Wu, Jianguang (Frontiers in Pharmacology, 2024)
Heart failure (HF) is a clinical condition caused by abnormalities in the heart's structure or function, primarily manifested as diminished ability of the heart to pump blood, which leads to compensatory activation of neurohormones and increased left ventricular filling pressure. HF is one of the fastest-growing cardiovascular diseases globally in terms of incidence and mortality, negatively impacting patients' quality of life and imposing significant medical and economic burdens. Despite advancements in the treatment of HF, hospitalization and mortality remain rates high. In China, Chinese herbal medicine (CHM) has historically played a prominent role in addressing HF, with significant proven efficacy. MicroRNA (miRNA) exerts a pivotal regulatory influence on the maintenance of regular cardiac activity and the progression of HF. MiRNAs, a category of single-stranded RNA molecules, are characterized by their inability to code for proteins. They regulate gene expression by binding to the 3'-untranslated region (3'-UTR) of target mRNAs, thereby influencing the onset and progression of various diseases. Abnormal expression of specific miRNAs is closely associated with HF pathological processes, such as cardiomyocyte apoptosis, myocardial fibrosis, and cardiac hypertrophy. This abnormal expression can influence the pathological progression of HF through the regulation of miRNA expression. This article reviews the regulatory role of miRNAs in HF pathology discusses how CHM compounds and their active ingredients can ameliorate HF pathology through the regulation of miRNA expression. In conclusion, miRNAs represent promising therapeutic targets for HF, and CHM provides a novel strategy for treatment through the regulation of miRNA expression. Future studies must delve deeper into the precise mechanisms by which CHM modulates miRNAs and fully explore its potential for clinical application in HF treatment.